Senescent Tumor Cells in the Peritoneal Carcinomatosis Drive Immunosenescence in the Tumor Microenvironment - Braumüller, Heidi; Mauerer, Bernhard; Berlin, Christopher; Plundrich, Dorothea; Marbach, Patrick; Cauchy, Pierre; Laessle, Claudia; Biesel, Esther; Holzner, Philipp Anton; Kesselring, Rebecca (Frontiers in Immunology, 2022)
More than half of all patients with colorectal cancer (CRC) develop distant metastasis and, depending on the local stage of the primary tumor, up to 48% of patients present peritoneal carcinomatosis (PC). PC is often considered as a widespread metastatic disease, which is almost resistant to current systemic therapies like chemotherapeutic and immunotherapeutic regimens. Here we could show that tumor cells of PC besides being senescent also show exhibit stem cell features. To investigate these surprising findings in more detail, we established a murine model based on tumor organoids that resembles the clinical situationsetting. In this murine orthotopic transplantation model for peritoneal carcinomatosis, we could show that the metastatic site in the peritoneum is responsible for senescence and stemness induction in tumor cells and that induction of senescence is not due to oncogenes oncogene activation or therapy. In both mouse and human PCBoth in mice and men, senescence in PC is associated with a senescence-associated secretory phenotype (SASP) influencing the tumor microenvironment (TME) of PC. SASP factors are able to induce a senescence phenotype in neighbouring cells. Here we could show that the SASP leads to enhanced immunosenescence in the TME of PC. Our results provide a new immunoescape mechanism in PC of colorectal cancer explaining the resistance of PC to known chemo- and immunotherapeutic approaches. Therefore, senolytic approaches may representbe a novel roadmapn interesting target to treat target this terminal stage of CRC.